PERAN ORANGTUA DAN GURU DALAM MENDIDIK ANAK TUNAGRAHITA YANG BERPRESTASI DI SLB SRI MUJINAB KOTA PEKANBARU - Vera, Okta; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Role is an attitude or behavior which is intended in this study is the role of parents and teachers. This study aims to find out how the role of parents in the home and the role of teachers in the school in educating the mentally retarded children, and also find out how motivated mentally retarded students to get achievements. The informants in this study are 8 persons, consisting of 3 mentally retarded children. 3 parents of the children, 2 teachers who taught and guided mentally retarded children and 1 principal as supporting data. In this study a purposive technique was used to determine the research subject with certain criteria, and for the data collection techniques, researchers use observation, interview and documentation. The results of the descriptive analysis show that mentally retarded children perform activities when they are going to participate in the competition by means of training that is guided directly by the teacher concerned and experts who have been appointed by the school. The appointment process of these children was chosen based on the classification of the mentally retarded children that was determined by the school and on the willingness of the mentally retarded children whitout coercion from any part. But, that does not mean the role of parents and teachers is not develop, because with encouragement and cooperation between parents and teachers can make this mentally retarded child get achievements at the Sri Mujinab extraordinary school Pekanbaru city. The role of parents at home is inseparable from providing moral, materil and creative support and supporting children when going to the race. While the role of the teacher in the school is to educate, guide, train and give motivation these children. The motivation from mentally retarded children to obtain achievement is they want to booast of their parents, teachers and also to boast of the name of the school, namely Sri Mujinab extraordinary school Pekanbaru city.Keywords: Mentally Disabled, Role, Motivation, Achievement